-8(k+6)=5k+2(k-4)

Simple and best practice solution for -8(k+6)=5k+2(k-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(k+6)=5k+2(k-4) equation:


Simplifying
-8(k + 6) = 5k + 2(k + -4)

Reorder the terms:
-8(6 + k) = 5k + 2(k + -4)
(6 * -8 + k * -8) = 5k + 2(k + -4)
(-48 + -8k) = 5k + 2(k + -4)

Reorder the terms:
-48 + -8k = 5k + 2(-4 + k)
-48 + -8k = 5k + (-4 * 2 + k * 2)
-48 + -8k = 5k + (-8 + 2k)

Reorder the terms:
-48 + -8k = -8 + 5k + 2k

Combine like terms: 5k + 2k = 7k
-48 + -8k = -8 + 7k

Solving
-48 + -8k = -8 + 7k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-7k' to each side of the equation.
-48 + -8k + -7k = -8 + 7k + -7k

Combine like terms: -8k + -7k = -15k
-48 + -15k = -8 + 7k + -7k

Combine like terms: 7k + -7k = 0
-48 + -15k = -8 + 0
-48 + -15k = -8

Add '48' to each side of the equation.
-48 + 48 + -15k = -8 + 48

Combine like terms: -48 + 48 = 0
0 + -15k = -8 + 48
-15k = -8 + 48

Combine like terms: -8 + 48 = 40
-15k = 40

Divide each side by '-15'.
k = -2.666666667

Simplifying
k = -2.666666667

See similar equations:

| 2(2x-5)=-6 | | 5(2X+3)=7X-6+2X | | 10x+33=5x+18 | | 3x(x-11)(2x+18)=0 | | 0.80x+0.50(80)=0.40(84) | | 120=3.5*x | | 6y=12-8x | | 4x^2+2.13=19.62 | | 6.75+.375x=13.25 | | 16x^2+22x+7=0 | | 16t^2-230t+110=0 | | 6.5-c=5 | | -2(3+x)+6x=6 | | f(x)=13x+2x-6 | | -8(w-2)=40 | | 180=4*7*5+2*5H | | v-x*x=w*w | | 2(4-3x)+5(2x)=20-5x | | -3(-8x+6)-8x=6(x-5)-2 | | 9x-14=6x+2 | | 12u^2-76uv+112v^2=0 | | 5x-3y=180 | | 16y+1=15y+2 | | A=law | | 8.25+.25w=10.75 | | 42y+7=32 | | A+64=92 | | 5x+8y=35000 | | 8u+2-4(-3u-2)=4(u-1) | | 19=-3+2x | | 7(-2)(-2)+4(-2)-5= | | -5x^2+2xy+3y^2=0 |

Equations solver categories